Evaluation of a Recovery Basic Income, and of a sustainable revenue neutral Citizen's Basic Income, with an appendix relating to different Universal Credit roll-out scenarios - Malcolm Torry (University of Essex, Institute for Social and Economic Research (ISER), 2020)
A Citizen's Basic Income, sometimes called a Basic Income, a Universal Basic Income, or a Citizen's Income, is an unconditional and nonwithdrawable income paid to every individual. There have been calls during the coronavirus crisis for both an Emergency Basic Income (an immediate Basic Income to protect individuals' incomes) and for a Recovery Basic Income (a Basic Income to be implemented with a view to preventing a recession once the virus outbreak begins to subside), and also for a permanent Citizen's Basic Income scheme. This working paper summarises the results of microsimulation research on a Recovery Basic Income and on a subsequent sustainable revenue neutral Citizen's Basic Income. An appendix studies the implementation of a Citizen's Basic Income scheme in the context of different Universal Credit roll-out assumptions.
Keywords: C80; H53; H55; I38; R20; 330; Citizen's Basic Income; microsimulation; UKMOD